Problematika Siswa Kelas Akselerasi : Studi kasus pada Siswa Kelas Akselerasi SD Hj Isriati Semarang - Liftiah, Liftiah (Intuisi : Jurnal Psikologi Ilmiah, 2009)
Awareness to optimalization the skill of student, especiallv about right of student to get good services which they have high capability and intelligent, has been formed acceleration program. This research will investigate and be focus to the problem of identification, the factor that cause appearance many problem in student of acceleration class d SD Hj Isriati Semarang, included how that solution. The characteristic of this research is exploration with case study approach Result of this research showed many problems appear in the beginning of class, especiallv socio emotional problem, like variation's emotional mature, emotional over excitabilities, more quite, dependent, difficuIt to make the decision less responsibility and less independently, always egoist and perfectionist. In the end of class appear academic problem like underachiever at Class VI. The other hand student of acceleration class have a positive character like more active, courageous and critical student, easy for acceptance the advice, high discipline, awareness and never doing the serious violation. The reason of socio emotional problem : young age people, over protective parents, over services, the parent wants to know all about their child business, determining the high standard score for their child. Underachiever causes by the change of learning system when the student was on Class VI, bored more claim and less commitment of task. Suggestions: to prepare the students for their socio emotionally development, like : confident, mature emotionally, independent, and task of commitment. The parents should be support and giving adequate assistance, giving good and harmonize parenting pattern at home with school’s parenting pattern. The parents should not give more claim about standard achievement for their child, but they must monitoring and giving motivation, sensitive with their child problem. If there was seen stress indication or bad behavior, as soon as possible to get consultation to the teacher or psychologist. For school and teacher have to monitoring the achievement development student of acceleration class and to created good teaching to increase the task commitment of student, so that can get the wonderful academic achievement.